(untitled) (El Hilo de la Fabula, 2022)
The publication in three volumes of the Complete Short Stories by Henry James in Spanish is a timely opportunity to analyze some translation guidelines by confronting five versions from different periods of James’s famous short story "The Death of the Lion".